Measurement of the Zakat Village Index in Curug Depok - Bahri, Efri Syamsul; Putri, Widya; P. Harto, Prayogo (Institut Agama Islam Negeri Kendari, 2021)
Zakat funds are a mandate of Allah SWT that must be distributed to mustahiq. This study aims to measure the feasibility of a village to be assisted by using zakat funds. The method used is a qualitative method using the Village Zakat Index (IDZ) model. The IDZ measurement includes five dimensions: economy, health, education, humanity, and dakwah. The research was conducted at Curug Depok. Data collection techniques were carried out through interviews, questionnaires, and expert judgment consisting of village officials, RT, and the community. The results showed that the IDZ value in Curug was categorized as functional with a score of 0.79. This finding indicates that Cukug is not prioritized to be assisted by zakat funds. The dimensions with the lowest IDZ value are the economic and human dimensions of 0.61 and 0.78. This data shows that zakat institutions can implement empowerment programs focusing on economic and humanitarian programs.